The Association between the Covid-19 Pandemic and the Number of Visits, Clinical Profile, and Treatment Costs on Pediatric Patients with Acute Gastroenteritis at dr. Soetomo General Hospital - Carisa Auralia Ramadhani; Anang Endaryanto; Ummi Maimunah (Indonesian Journal Publisher, 2026)
The COVID-19 pandemic disrupted healthcare utilization and may have influenced the clinical characteristics and treatment costs of pediatric acute gastroenteritis (AGE). This study aimed to evaluate changes in the number of visits, clinical profiles, and treatment costs of pediatric AGE patients pre-, during, and post- the COVID-19 pandemic at Dr. Soetomo General Academic Hospital, Surabaya. Methods: A retrospective observational comparative study was conducted using medical records of pediatric AGE patients (≤18 years old) treated at Dr. Soetomo General Hospital. A total of 3,721 patients who met the inclusion and exclusion criteria were included. Data were compared across the pre-pandemic, pandemic, and post-pandemic periods using the Kruskal–Wallis test, followed by the Mann–Whitney U test. Results: Among the 3,721 patients, the mean monthly visits decreased from 91.8 patients pre-pandemic to 59.2 patients during the pandemic (p < 0.05). The mean number of comorbidities increased from 3.91 to 4.68 during pandemic, particularly among hospitalized patients (p < 0.05). The mean total treatment costs increased from IDR 3,74 million to IDR 7,56 million during the pandemic. Discussion: The COVID-19 pandemic significantly affected healthcare utilization, clinical characteristics, and treatment costs among pediatric AGE patients. These findings may help guide healthcare planning, resource allocation, and the development of strategies during future public health emergencies.